Half-Space Relaxation Projection Method for Solving Multiple-Set Split Feasibility Problem - Guash Haile Taddele; Poom Kumam; Anteneh Getachew Gebrie; Kanokwan Sitthithakerngkiet (Mathematical and Computational Applications, 2020)
In this paper, we study an iterative method for solving the multiple-set split feasibility problem: find a point in the intersection of a finite family of closed convex sets in one space such that its image under a linear transformation belongs to the intersection of another finite family of closed convex sets in the image space. In our result, we obtain a strongly convergent algorithm by relaxing the closed convex sets to half-spaces, using the projection onto those half-spaces and by introducing the extended form of selecting step sizes used in a relaxed CQ algorithm for solving the split feasibility problem. We also give several numerical examples for illustrating the efficiency and implementation of our algorithm in comparison with existing algorithms in the literature.